1998
DOI: 10.1523/jneurosci.18-16-06207.1998
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Cultured Neurons from Amyloid Precursor Protein Knock-Out Mice against Alzheimer’s Amyloid-β Toxicity and Oxidative Stress

Abstract: Studies on the amyloid precursor protein (APP) have suggested that it may be neuroprotective against amyloid-beta (Abeta) toxicity and oxidative stress. However, these findings have been obtained from either transfection of cell lines and mice that overexpress human APP isoforms or pretreatment of APP-expressing primary neurons with exogenous soluble APP. The neuroprotective role of endogenously expressed APP in neurons exposed to Abeta or oxidative stress has not been determined. This was investigated using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
71
0
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 56 publications
4
71
0
1
Order By: Relevance
“…APP belongs to a multigene family that includes the two amyloid precursor-like proteins 1 and 2 (APLP1 and APLP2) (4,(43)(44)(45). Most of the functional domains and structural motifs found in APP are also present in APLPs (particularly APLP2) (60), suggesting that they may share common biological functions in neurons. Using the monoclonal antibody 22C11, several studies have reported that this antibody cannot discriminate between APP and APLP2 (45,60,61).…”
Section: App-ab-dependent Pcd Is Distinct From Apoptosis-thismentioning
confidence: 99%
“…APP belongs to a multigene family that includes the two amyloid precursor-like proteins 1 and 2 (APLP1 and APLP2) (4,(43)(44)(45). Most of the functional domains and structural motifs found in APP are also present in APLPs (particularly APLP2) (60), suggesting that they may share common biological functions in neurons. Using the monoclonal antibody 22C11, several studies have reported that this antibody cannot discriminate between APP and APLP2 (45,60,61).…”
Section: App-ab-dependent Pcd Is Distinct From Apoptosis-thismentioning
confidence: 99%
“…Cortical cultures were prepared as described previously (White et al, 1998). In brief, embryonic day 14 C57BL6Jx 129sv mouse cortices were removed, dissected free of meninges, and dissociated in 0.025% (wt/vol) trypsin.…”
Section: Primary Neuronal Culturesmentioning
confidence: 99%
“…At day 5 in vitro, BSO (0.01-I00 p M ) was added to the culture medium with or without CuCl,,FeCI,,or FeC1,. After 16 h at 37"C, cell viability was determined using the MTT assay as described previously (White et al, 1998). We have found that the MTT assay provides an accurate indication of neuronal viability under the conditions used and compares favorably with other viability assays such as Alamar Blue method.…”
Section: Gsh Depletion and Transition Metal Treatmentmentioning
confidence: 99%
“…In APP-and APLP2-knockout mice, Cu levels were found increased in cerebral cortex and liver, whereas overexpression of APP was reported to result in significantly reduced Cu levels in the Tg2576 line (17)(18)(19). Depending on the conservation of the CuBD, Cu was also found to influence APP processing in cells when Cu greatly reduced the levels of amyloid A␤, and caused an increase in the secretion of the APP ectodomain (20,21).…”
mentioning
confidence: 99%